Involvement of Interleukin-1 Receptor-Associated Kinase 4 and Interferon Regulatory Factor 5 in the Immunopathogenesis of SARS-CoV-2 Infection: Implications for the Treatment of COVID-19 - Stoy, Nicholas (Frontiers in Immunology, 2021)
Interleukin-1 receptor-associated kinase 4 (IRAK4) and interferon regulatory factor 5 (IRF5) lie sequentially on a signalling pathway activated by ligands of the IL-1 receptor and multiple TLRs located either on plasma or endosomal membranes. Activated IRF5, in conjunction with other synergistic transcription factors, notably NF-κB, is crucially required for the production of proinflammatory cytokines in the innate immune response to microbial infection. The IRAK4-IRF5 axis could therefore have a major role in the induction of the signature cytokines and chemokines of the hyperinflammatory state associated with severe morbidity and mortality in COVID-19. Here a case is made for considering IRAK4 or IRF5 inhibitors as potential therapies for the ‘cytokine storm’ of COVID-19.